Expressions of dependency: green crimes and the phantasmagoria of 'development' in the extreme west of Bahia, Brazil - Pôssas, Isabela Braichi (Criminological encounters, 2022)
The article establishes a critical analysis of development and dependency and the forms of appropriationof common goods and extraordinary profit as centralities of the monopolistic capital’s activitiesin the Brazilian countryside. From a reflection on the elements of dependency, the article identifies the main territorial determinations which arise from the productive internationalisation that is internalised in peripheral economies. The empirical basis of analysis is the extreme west of Bahia, the most intensive area of water extraction for soybean production in the Matopiba region. It is evident that the main territorial determinations of dependency in the context of appropriation of common goods are established based on the expansion of the productive matrix, landscape homogenisation, land speculation, water grabbing, violence and conflicts in the field, which, on the one hand, check the concept of development and, on the other hand, make the character of the dependency explicit.